STRATEGI PEMBELAJARAN SKIIL BERBAHASA INGGRIS BERBASIS GAYA BELAJAR UNTUK MENINGKATKAN KEMAMPUAN MAHASISWA DALAM BERBAHASA INGGRIS - Fithriyah Fithriyah; Subhan; M. Chalis; Nurjanah Ismail; Mujiburrahman (STAI Nusantara Kota Banda Aceh, 2026)
English language proficiency is one of the key competencies for students in the era of globalisation. However, the process of learning English often faces various obstacles, such as low motivation to learn, monotonous teaching methods, and differences in students’ learning styles. One approach that can be applied to address these issues is a learning strategy based on learning styles. This article aims to analyse English language skills learning strategies tailored to students’ learning styles in order to improve their English language proficiency. The method used in this article is a literature review, examining various theories and research findings related to learning styles and English language learning. The findings indicate that the implementation of learning strategies suited to visual, auditory, and kinesthetic learning styles can improve students’ motivation, participation, and learning outcomes. Therefore, lecturers need to understand the characteristics of students’ learning styles so that the English language learning process becomes more effective and optimal.